Adjuvant antithrombotic therapy in ST-elevation myocardial infarction : contemporaneous portuguese cross-sectional data - Caldeira, Daniel (2019)
© 2020 Sociedade Portuguesa de Cardiologia. Published by Elsevier España, S.L.U. This is an open access article under the CC-BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).